INFORMATION SYSTEM OF MARKETING MANAGEMENT AT REYMART GROCERY STORE BASED ON ENTERPRISE ARCHITECTURE PLANNING METHOD - Lakasamana Bangsawan; Julia Safitri; Sri Surya Mandala; Rita Irviani (Jurnal TAM (Technology Acceptance Model), 2020)
Grocery stores are currently experiencing increasingly fierce competition in the business world, which makes business people have to think hard in formulating strategies to face competition. In formulating a profitable strategy, business people can take advantage of technology. The utilization of technology and information is also very necessary for an organization or company. This is necessary because the development of increasingly rapid and complex information systems will affect the processes and business developments that are currently running. Therefore, one way to meet business needs in accordance with the organization's business development is to develop an enterprise architecture that uses a methodology such as Enterprise Architecture Planning (EAP). This methodology is a method used to approach data quality planning by looking at the business needs of the organization. The outputs produced are in accordance with the expected results and can describe stakeholder goals in describing plans to develop a system or set of systems. In this study, the author uses the Enterprise Architecture Planning (EAP) method to support the business and plan to implement the architecture. The architecture here is like blueprints and drawings or models. The blueprint generated from the Enterprise Architecture Planning (EAP) process will be used as a guide for the creation of a blueprint in strategic planning for the Management Information System and overall marketing at the Reymart store.